2011
DOI: 10.1007/s10029-011-0869-y
|View full text |Cite
|
Sign up to set email alerts
|

Sutureless hernioplasty with light-weight mesh and fibrin glue versus Lichtenstein procedure: a comparison of outcomes focusing on chronic postoperative pain

Abstract: Our experience shows that the combined use of light-weight mesh and fibrin glue gives significantly better results in terms of postoperative pain and return to daily life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
5

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 19 publications
(19 reference statements)
1
37
0
5
Order By: Relevance
“…Six studies reported the incidence of chronic pain after inguinal hernia repair [1,8,9,12,13,14]. Five of them reported a lower percentage of chronic pain in the fibrin group, while only one study [14] reported a higher percentage of chronic pain.…”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…Six studies reported the incidence of chronic pain after inguinal hernia repair [1,8,9,12,13,14]. Five of them reported a lower percentage of chronic pain in the fibrin group, while only one study [14] reported a higher percentage of chronic pain.…”
Section: Resultsmentioning
confidence: 96%
“…The recurrence rate in these trails was 1.79% [11], 0.95% [9], 1.35% [8], 0.38% [14] and 0.98% [15], respectively, with the follow-up of 6 to 15 months. One trial [8] determined the recurrence by clinical examination, while others didn't provide specific methods. Five recurrences in the fibrin group and four recurrences in the suture group were found.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations